New Zealand Nurses' Perceptions of Spirituality and Spiritual care: Qualitative Findings from a National Survey - Egan, Richard (Religions, 2017)
This paper presents the qualitative findings from the first national survey of New Zealand nurses' views on spirituality and spiritual care. The importance of spirituality as a core aspect of holistic nursing care is gaining momentum. Little is currently known about New Zealand nurses' understandings, perceptions and experience of spirituality. Design: A descriptive online survey. Method: A random sample of 2000 individuals resident in New Zealand whose occupation on the New Zealand electoral roll suggested nursing was their current or past occupation were invited via postcard to participate in an online survey. This paper reports on the free response section of the survey. Findings: Overall, 472 invitees responded (24.1%). From the respondents, 63% completed at least one of the optional free response sections. Thematic analysis generated three metathemes: The role of spirituality in nursing practice', Enabling best practice', and Creating a supportive culture'. Conclusions: Spirituality was predominantly valued as a core aspect of holistic nursing care. However, clarity is needed surrounding what constitutes spiritual care and how this intersects with professional responsibilities and boundaries. Participants' insights suggest a focus on improving the consistency and quality of spiritual care by fostering inter-professional collaboration, and improved provision of resources and educational opportunities.